Computational design, docking, and molecular dynamics simulation study of RNA helicase inhibitors of dengue virus - Raghunath Satpathy; Sonali Acharya; Rashmiranjan Behera (Journal of Vector Borne Diseases)
Background & objectives: RNA viruses are complex pathogens in terms of their genetic makeup, mutation frequency, and transmission modes. They contain the RNA helicase enzyme, which plays a crucial role in the viral genome replication process. This work aims to develop and screen a potential molecule that could function as a dengue virus (DENV) RNA helicase inhibitor. Methods: The present study was performed by taking 26 potential derivatives of gedunin phytochemicals from the PubChem database as ligands. The binding of the compounds was analyzed by in silico docking considering DENV RNA helicase enzyme as the receptor. Results: After a thorough analysis of the docking scores, toxicity, and physicochemical properties, the compound tetrahydrogedunin was obtained as the best. Based on tetrahydrogedunin molecular structure, 100 drug-like molecules were designed using the Data Warrior tool. After screening for drug-likeness and ADMET properties, derivative number 42 was considered as promising. Further comparative docking of derivative 42 and a standard inhibitor molecule ST-610 with DENV RNA helicase enzyme showed binding affinity of 10.0 kcal/mol and -9.6 kcal/mol, respectively. The favorable interaction between DENV RNA helicase and derivative 42 was further validated by 50 nanoseconds molecular dynamics simulation and MM-GBSA analysis. Interpretation & conclusion: Since the antiviral activity of derivative 42 has not been reported till date, the compound was predicted as a novel therapeutic molecule that can act against the dengue virus (DENV) RNA helicase enzyme.